Customer satisfaction and perceived service quality in Nepal’s banking sector - Chhetri, Ashmita Dahal (Journal of Balkumari College, 2024)
This study examines the variables influencing client satisfaction in the Chitwan of commercial banking in Nepal. With the use of standardized questionnaires, a sample of 250 bank customers was surveyed. The findings demonstrated that banks are thought to provide accurate, timely services along with efficient record-keeping and problem-solving. Regarding the other hand, opinions regarding personnel availability and responsiveness vary. Convenience and accessibility are highlighted by high empathy scores, yet there is a noticeable perceptual difference. While most people agree on the importance of assurance in customer service, perspectives on staff professionalism and confidence differ. Though there is room for development in terms of clarity and multi-channel use, communication on service changes is successful. According to the study, there is a lesser correlation between empathy and customer satisfaction and high positive correlations with assurance, communication, trustworthiness, responsiveness, and reliability. Regression research shows that tangibility has a favorable impact on customer satisfaction, and that reliability, empathy, assurance, communication, tangibility, and credibility have a substantial impact as well. The results highlight how better client retention tactics are required to raise consumer happiness and loyalty.